Optical water types of the Nordic Seas and adjacent areas - Aas, Eyvind; Højerslev, Niels Kristian; Høkedal, Jo; Sørensen, Kai (Oceanologia, 2013)
Embargoed access on accepted manuscript version, under Creative Commons licence Link to publisher's version: https://doi.org/10.5697/oc.55-2.471 A new map of Jerlov's optical water types in the Nordic Seas and adjacent waters at 139 locations, as well as a table with statistical and geographical properties of the vertical attenuation coefficient of downward irradiance at 475 nm, are presented. The data analysis is based on 715 recordings at different stations, at latitudes between 54° and 82°N, and longitudes between 31°W and 49°E, obtained by different authors from May 1954 to August 2003. The results show that the Atlantic and Polar waters are typically of oceanic type II-III, although during algal blooms the optical conditions may change to coastal types 1, 3 and 5, which are also the most frequent types found in coastal areas.